1980
DOI: 10.1017/s0014479700011005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Liming and Soil pH on Guinea Grass (Panicum maximum) in Malaysian Tropical Oligotrophic Peat

Abstract: SUMMARYIn a three-year field experiment on acid peat (pH 3.47) up to 12 t/ha lime increased peat pH (0–30 cm depth) by 0.061/t. Annual guinea grass dry matter increased in quadratic relation with liming up to pH 4.20 (12 t/ha lime) but there was no difference between the cvs Sigor and Colonoa. Liming decreased the N, P and K, but increased the Ca and Mg contents of the harvested grass. Liming also increased the uptake of all five nutrients investigated, either linearly or curvilinearly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…However, in all three seasons of Expt 2, where the natural peat pH was 3.78, liming reduced tuber DM with little difference between 10 and 20 t/ha lime. These results confirm earlier reports (Edwards et al; Spain et al) that cassava is highly tolerant of soil acidity per se and on peat has proved to be more so than tobacco, Guinea grass, sorghum and groundnut (Chew et al, 1980a and1980b;W. Y. Chew et al, unpublished).…”
Section: Experiments 1 and 2: Effects Of Peat Ph On 10-month-old Cassavasupporting
confidence: 91%
“…However, in all three seasons of Expt 2, where the natural peat pH was 3.78, liming reduced tuber DM with little difference between 10 and 20 t/ha lime. These results confirm earlier reports (Edwards et al; Spain et al) that cassava is highly tolerant of soil acidity per se and on peat has proved to be more so than tobacco, Guinea grass, sorghum and groundnut (Chew et al, 1980a and1980b;W. Y. Chew et al, unpublished).…”
Section: Experiments 1 and 2: Effects Of Peat Ph On 10-month-old Cassavasupporting
confidence: 91%
“…Liming to raise soil pH is therefore essential to optimize yields. In these experiments, sweet potato produced optimum tuber and vine DM at pH 5.5 (Figs 4a and b) which is comparable to the pH optima earlier obtained on peat for tobacco (5.25; Chew et al, 1980b) and sorghum (5.7; Chew et al, 1981b), but appreciably higher than for pineapple (pH 3.0-3.5; Tay, 1972) and cassava (3.8; Chew et al, 1980c), while groundnut and guinea grass are intermediate in sensitivity to peat acidity (pH optima 4.6 and 4.2, respectively; Chew et al, 1980c and1981a).…”
supporting
confidence: 82%
“…It was also concluded that 100 ppm of Cu, both as a fertilizer and mitigator of subsidence, could be added to these soils at a stabilized pH of 3.4 to 3.6 without adverse effects on plant nutrition. At lower pH, the Cu concentration of the crop was found to increase from an optimal 10 ppm to 17 (Valk 1973;Rayment and Chancey 1966;O'Toole 19'72;Mclean et al 1963Mclean et al , 1973Jasmin and Heeney 1962;Hamilton and Bernier 1973;Gupta et al 1978;Lucas et al 1974;Van Lierop et al 1980: Chew et al 1980, 1981Adams et al 19'78;Otabbong 1980;Mathur 1982b;Healy 1980 (Mills 1975 (Mathur 1982a, b;Levesque and Mathur 1982;Ma-thur Mathur et al 1919). …”
mentioning
confidence: 99%
“…I , 2). This was because the soil pH did not exceed 6.0 (Table 2) where the mobility and availability of Cu in organic soils begins to decline (Lucas and (3.8-4.0) found to be suitable for growing Guinea-grass on an oligotrophic peat (Chew et al 1980 (Millar 1955 …”
mentioning
confidence: 99%